Answer:
B) 42
Step-by-step explanation:
Area =
b h
Area =
x 12 x7
Area = 42
Answer:
B. 18
Step-by-step explanation:
For the function
![f(x)=\left\{\begin{array}{l}x+9,\ \ x](https://tex.z-dn.net/?f=f%28x%29%3D%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bl%7Dx%2B9%2C%5C%20%5C%20x%3C9%5C%5C27-x%2C%5C%20%5C%20x%5Cge%209%5Cend%7Barray%7D%5Cright.)
we can find the value of the function for all x that are very close to 9 but are less than 9 and for all values of x that are very close to 9 but are greater than 9.
1. For ![x](https://tex.z-dn.net/?f=x%3C9%3A)
![\lim \limits_{x\rightarrow 9}f(x)=\lim \limits_{x\rightarrow 9}(x+9)=9+9=18](https://tex.z-dn.net/?f=%5Clim%20%5Climits_%7Bx%5Crightarrow%209%7Df%28x%29%3D%5Clim%20%5Climits_%7Bx%5Crightarrow%209%7D%28x%2B9%29%3D9%2B9%3D18)
2. For ![x\ge 9:](https://tex.z-dn.net/?f=x%5Cge%209%3A)
![\lim \limits_{x\rightarrow 9}f(x)=\lim \limits_{x\rightarrow 9}(27-x)=27-9=18](https://tex.z-dn.net/?f=%5Clim%20%5Climits_%7Bx%5Crightarrow%209%7Df%28x%29%3D%5Clim%20%5Climits_%7Bx%5Crightarrow%209%7D%2827-x%29%3D27-9%3D18)
So, limit exists and is equal to 18.
Answer:
6.59 and 3.41
Step-by-step explanation:
To evaluate, substitute n for each of the given values.
So when n= 3:
0.53n + 5 = 1.59 + 5 = 6.59
And when n = -3
0.53 n + 5 = -1.59+5=3.41
Hope this helps
Answer:
x=4 hope this helps
Step-by-step explanation:
Answer: The value of k for which one root of the quadratic equation kx2 - 14x + 8 = 0 is six times the other is k = 3.
Let's look into the solution step by step.
Explanation:
Given: A quadratic equation, kx2 - 14x + 8 = 0
Let the two zeros of the equation be α and β.
According to the given question, if one of the roots is α the other root will be 6α.
Thus, β = 6α
Hence, the two zeros are α and 6α.
We know that for a given quadratic equation ax2 + bx + c = 0
The sum of the zeros is expressed as,
α + β = - b / a
The product of the zeros is expressed as,
αβ = c / a
For the given quadratic equation kx2 - 14x + 8 = 0,
a = k, b = -14, c = 8
The sum of the zeros is:
α + 6α = 14 / k [Since the two zeros are α and 6α]
⇒ 7α = 14 / k
⇒ α = 2 / k --------------- (1)
The product of the zeros is:
⇒ α × 6α = 8 / k [Since the two zeros are α and 6α]
⇒ 6α 2 = 8 / k
⇒ 6 (2 / k)2 = 8 / k [From (1)]
⇒ 6 × (4 / k) = 8
⇒ k = 24 / 8
⇒ k = 3